1990
DOI: 10.1130/spe247-p595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of late Eocene impacts on planktic foraminifera

Abstract: A series of iridium anomalies and microtektite-bearing layers indicative of extraterrestrial impact events have been found in late Eocene sediments in the deep sea. Previously, these deposits had been reported to be approximately synchronous with major extinction events in groups of both terrestrial and marine organisms. Highresolution biostratigraphic studies, though, have failed to find any direct evidence for association between impact-derived materials and species extinctions in individual stratigraphic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The index species used to define these biozone boundaries are shown in Figure 10. This stratigraphic refinement improves the relative age correlation and in Montanari, 1988, 1990. particular aids in the stratigraphic placement of the impact horizons which were found in the late Eocene.…”
Section: Chronostratigraphy and Biostratigraphymentioning
confidence: 77%
“…The index species used to define these biozone boundaries are shown in Figure 10. This stratigraphic refinement improves the relative age correlation and in Montanari, 1988, 1990. particular aids in the stratigraphic placement of the impact horizons which were found in the late Eocene.…”
Section: Chronostratigraphy and Biostratigraphymentioning
confidence: 77%
“…According to some authors, a crater this size could be expected to cause a mass extinction of 45 percent of the marine life on Earth (Raup, 1991a,b). Extensive studies of late Eocene biotic events during the past ten years have shown conclusively, however, that no such mass extinction took place during biochron P15 (MacLeod, 1990;Miller et al, 199 1;Prothero and Berggren, 1992;Jansa, 1993).…”
Section: Altered Paleoenvironmentsmentioning
confidence: 99%
“…Thus, these planktic foraminiferal data also fail to support the contention of Gould (1985) and Raup (1986Raup ( , 1991 that mass extinction events in general, and the K/T event in particular, derive from fundamental changes in the nature of selection pressures brought on by intermittent collisions with extraterrestrial objects such that previously well-adapted species (or morphotypes) lose their competitive edge in the face of extraordinary environmental circumstances. MacLeod (1990) analyzed the temporal dynamics of the Eocene -Oligocene turnover, concluding that: i.) the turnover took place over at least eight different planktic Downloaded by [University of Calgary] at 06:25 03 February 2015 foraminiferal biozones that, together represent almost 12 m.y.…”
Section: Discussionmentioning
confidence: 99%